The Compactness and Inboard Radial Build of Fusion Nuclear Devices. (17th November 2021) - Kessel, C. E.; Bohm, T.; Tillack, M. S.; Titus, P.; Zhai, Y.
Abstract: Restraining the size of fusion power plants is considered an important avenue to make them a competitive energy source among other forms of energy production. The most critical contributor to the size of a tokamak is the inboard radial build, composed of multiple components with various functions. This build is the ultimate limit to size reduction. The Fusion Nuclear Science Facility is reviewed and each element of the inboard build is described, showing that the build, including breeding blanket, structural ring, vacuum vessel, low-temperature shield, and toroidal field and central solenoid (CS) coils, contributes 2.9 m of build, with 0.6 m of bore hole inside the CS coil, or 3.5 m to reach the plasma scrape-off layer. This implies that it would be challenging to make a significantly smaller build and simultaneously meet all the engineering requirements.